The development of retirement center in Malaysia: lesson from Japan - Abdullah Sukri, Muhammad Mukmin; Utaberta, Nangkula; Mohd Sohimi, Fatin Wafaa; Mohd Yunus, Mohd Yazid; Ismail, Nor Atiah; Ismail, Sumarni (American-Eurasian Network for Scientific Information, 2015)
The main objective of this paper is to look up the development of retirement centre or nursing homes in Malaysia with reference to Japan. The paper provides historical studies which have been analysed in this paper to show the benchmark for Malaysia. Some improvements of retirement center are developed throughout the case studies taken from other countries. This paper aims to give a picture of Malaysia elderly health care system in the future so that proper steps would be taken for a better retirement center.